Increased Glycan Chain Length Distribution and Decreased Susceptibility to Moenomycin in a Vancomycin-Resistant Staphylococcus aureus Mutant - Komatsuzawa, Hitoshi (American Society for Microbiology, 2002)
A vancomycin-resistant Staphylococcus aureus mutant, COL-VR1 (MIC, 16 μg/ml), was isolated from methicillin-resistant S. aureus COL by exposure to vancomycin. COL-VR1 also showed decreased susceptibility to teicoplanin (8-fold), methicillin (2-fold), macarbomycin (8-fold), and moenomycin (16-fold). Macarbomycin and moenomycin are thought to directly inhibit transglycosylase activity. Characterization of the mutant revealed a thickened cell wall and suppression of penicillin-induced lysis, although the amounts of the five penicillin-binding proteins (PBPs 1, 2, 3, 4, and 2′) and the profiles of peptidoglycan hydrolases were not altered. Analysis of muropeptide profile and glycan chain length distribution by reversed-phase high-pressure liquid chromatography revealed slightly decreased peptide cross-linking and an increased average glycan chain length compared to those of the parent. These results together suggest that a transglycosylase activity was enhanced in the mutant. This may represent a novel mechanism of glycopeptide resistance in S. aureus.